2020
DOI: 10.3389/fpsyt.2020.00866
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Epidemic in Argentina: Worsening of Behavioral Symptoms in Elderly Subjects With Dementia Living in the Community

Abstract: necessary to develop a plan of action to help dementia subjects deal with the increased stress that this epidemic imposed on them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 30 publications
3
107
3
5
Order By: Relevance
“…Changes in medication were reported in 26% of the cases. This is close to the 27% increase reported by Cagnin et al, (Cagnin et al, 2020), the 20% increase reported by Cohen et al (Cohen et al, 2020) and far higher than the 7% reported by Canevelli et al (Cavenelli et al, 2020). As in previous studies, many of the changes had to do with commencement or increase in the use of antipsychotics, benzodiazepines and antidepressants.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Changes in medication were reported in 26% of the cases. This is close to the 27% increase reported by Cagnin et al, (Cagnin et al, 2020), the 20% increase reported by Cohen et al (Cohen et al, 2020) and far higher than the 7% reported by Canevelli et al (Cavenelli et al, 2020). As in previous studies, many of the changes had to do with commencement or increase in the use of antipsychotics, benzodiazepines and antidepressants.…”
Section: Discussionsupporting
confidence: 85%
“…The questions were informed by emerging evidence from research in the field (Lara et al, 2020; Canevelli et al, 2020; Cohen et al, 2020; Boutoleau-Bretonniere et al, 2020; Cagning et al, 2020) and feedback from the experience of the Direct Support Team at RDS and clinical experience. Three variations in the survey questions were produced to suit the three types of respondents approached:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the social restrictions and increased isolation may lead to increased negative effects on memory disorders and neuropsychiatric symptoms of older people with NCD (18,19). In fact, recent data on this topic reported an increase of behavioral symptoms in elderly with dementia (8)(9)(10). It is also possible that there may be an increased need for assessment of new patients in geriatric psychiatry settings as a result of the negative consequence of quarantine and social distancing measures.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have employed similar restrictive measures (2-4) and have made changes to the routine management of patients with non-communicable diseases [e.g., canceling "so-called" non-urgent appointments, which have important implications for the identification and treatment, and therefore for the progression of these chronic conditions (5)]. Although the focus on procedures to urgently slow SARS-CoV-2 infection rates and minimize the number of infected individuals has extreme importance, it has short-and long-term negative consequences on health and well-being of patients with non-communicable diseases, including neurocognitive disorders (NCD) (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%